(untitled) (Psychology Travelogs, 2024)
The article provides a theoretical analysis of the psychological features that influence the formation of the image and reveal in this professional field are determined. We have analyzed the main functions of the professional image are defined, among which the following are important: professional self-identification and belonging; professional training and self-development; professional control and self-management of one’s own behavior; professional self-expression and self-presentation. The structural components of the image: external attributes (clothing style, accessories, hairstyles); internal characteristics (moral, ethical and spiritual attitudes); individual psychological features; interpersonal aspects such as self-presentation skills and communication skills. The main groups of psychological indicators-criteria, which form the professional image of specialists in socionomic professions: individual personality properties: purposefulness, confidence; professional qualities: oratorical skills, conflict resolution, ability to lead discussions; socio-psychological qualities: publicity, status. It is established that the modern image of specialists in the socionomic field is characterized by a number of psychological features, including professional competence, empathy, understanding, proactivity, initiative, professional ethics, flexibility, adaptability, innovativeness and effective communication. Psychological recommendations have been developed that will contribute to the development of the psychological readiness of specialists in the socionomic field to improve the individual image and facilitate the process of adaptation in society. We see the prospects for further research in the development of psychological support for the development of the modern image of specialists in the socionomic sphere.